2011
DOI: 10.1007/s12072-010-9244-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection among patients with non-Hodgkin’s lymphoma in northern India

Abstract: Background and aim Hepatitis C virus (HCV) has been postulated to be an etiological agent for lymphoid malignancies. Whereas a high prevalence of HCV infection in non-Hodgkin's lymphoma (NHL) patients has been shown to exist in many geographical areas of high HCV prevalence, studies from other parts have not established any form of association. In India, there is a scarcity of data to show either a positive or a negative association between NHL and HCV infection. Therefore, we determined the prevalence of HCV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In contrast, other studies, conducted in France (36), Canada (37) and India (38,39), found no or weak association between HCV infection and subtypes of NHL. These studies were limited by small sample sizes and In our study, we observed that the risk of having lymphoproliferative disorders was greater with HCV infection (OR = 2.67) than with pesticides exposure (OR= 2.24).…”
Section: ‫املتوسط‬ ‫لرشق‬ ‫الصحية‬ ‫املجلة‬ ‫العرشون‬ ‫املجلد‬ ‫السادmentioning
confidence: 74%
“…In contrast, other studies, conducted in France (36), Canada (37) and India (38,39), found no or weak association between HCV infection and subtypes of NHL. These studies were limited by small sample sizes and In our study, we observed that the risk of having lymphoproliferative disorders was greater with HCV infection (OR = 2.67) than with pesticides exposure (OR= 2.24).…”
Section: ‫املتوسط‬ ‫لرشق‬ ‫الصحية‬ ‫املجلة‬ ‫العرشون‬ ‫املجلد‬ ‫السادmentioning
confidence: 74%
“…HCV association with B cell NHL is still a matter of debate, no association between HCV infection and B cell NHL was found [8,9]. Most of the studies that failed to find an association of HCV with B cell NHL were conducted in areas where the prevalence of HCV is extremely low; leaving open the possibility that such an association actually exists but could not be detected because neither cases nor controls had adequate opportunity for exposure to the virus [10].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies reported to date failed to find an association of HCV with NHL were conducted in areas where the prevalence of HCV was extremely low, leaving open the possibility that such an association actually exists but could not be detected because neither cases nor controls had adequate opportunity for exposure [8,9,10]. Working in a population with high prevalence of HCV allowed us to conduct a casecontrol study with adequate statistical power to assess the question of whether there is an association of chronic HCV infection with NHL [11].…”
Section: Introductionmentioning
confidence: 99%
“…B oth the hepatitis B virus (HBV) and hepatitis C virus (HCV) have been implicated in the pathogenesis of chronic lymphocytic leukemia (1)(2)(3). In support of this hypothesis are: epidemiological data describing associations between each virus and other hematological malignancies; the presence of viral replicative intermediates in peripheral blood mononuclear cells; and findings that each virus encodes for proteins with oncogenic potential (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). However, studies specifically designed to document the prevalence of HBV and/or HCV in patients with chronic lymphocytic leukemia are limited and have reported variable results (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%